Analysis of the effectiveness of the content filter algorithm in the TikTok Shop application for UMKM - gizza khairani khairani; Beby Dwiyanti; Nazwa Annisa; Supina Batubara (Journal of Information Technology, computer science and Electrical Engineering, 2024)
With the rapid development of the TikTok social media application, especially on the e-commerce platform, often called the TikTok shop, which is the public's choice for shopping online, it is important to understand how the content filter algorithm can influence the visibility and success of UMKM on this platform. TikTok Shop it self has become a hot topic of conversation among the public, which is a hot topic and is the target market for e-commerce platforms. The high volume of content uploaded every day is a new challenge that arises to ensure that the content presented is in line with UMKM brand standards and values. This also aims to show that the content filter algorithm in TikTok Shop has a significant role in helping UMKM maintain products as well as to avoid inappropriate content. It has been found that several UMKM face obstacles in understanding the policies and procedures set by the TikTok Shop algorithm, as well as difficulties in optimizing content visibility. Therefore, researchers are interested in conducting an analysis regarding the effectiveness of the content filter algorithm in the TikTok Shop application on Micro, Small and Medium Enterprises (UMKM).